Depression in older adults: prevalence and psychosocial risk factors in rural and urban settings in the province of Misiones, Argentina - Viviana Salinas, Angélica (2020)
Current research indicates that the changes that accompany aging (feeling of insecurity, modification of lifestyle, restriction of the social environment, loss of family and friends, and less psycho-physical autonomy) may favor the appearance of depressive symptoms. However, there are few studies that address this issue, including rural areas. Therefore, the present work seeks to identify the risk of depression and predisposing psychosocial factors in older adults in rural and urban settings. Therefore, the present work seeks to identify the risk of depression and predisposing psychosocial factors in older adults in rural and urban settings. For this purpose, a descriptive-comparative study was carried out. 80 people over 65 from rural and urban areas in the south of the province of Misiones participated. Depression was assessed with the GDS-15, and predisposing factors with a semi-structured interview. The risk of depression was estimated using descriptive statistics, and the comparison of depressive state and risk factors between the samples was analyzed with the t and Chi2 tests. Regression analysis was used to determine the predictive weight of risk factors for depression. This study showed normal and mild values of depression in both samples, with greater preponderance in the urban segment (light-moderate level). The main predisposing factors in the rural population are low spirituality, socioeconomic status, and recent grief; and in the urban sample, the lack of purpose in life and recent duels. Increased propensity for depression was observed in urban adults, with levels reaching moderate depression in some cases. The difference may be due to the fact that urban older adults, although they have a somewhat better socioeconomic level, perceive less social support, experience greater loneliness, have a less clear and defined purpose in life, and a lesser sense of spirituality.